Understanding Time Engagement Dynamics via Virtual Socialization on Instagram - Bhattacharjee, Sandeep (Indian Journal of Computer Science, 2022)
The emergence of social media in the past decade owing to faster internet and accessibility devices has led to the influx of the modern generation into the web of virtual social presence. The various popular social media include Facebook, Instagram, and Twitter. In this research paper, we have tried to carry out a microscopic study for ascertaining the engagement of today’s youth in terms of spending time on different activities on Instagram. A sample survey was performed on 105 samples using random probability sampling which yielded some fruitful results. The age group of 21 to 25 years mainly comprising of postgraduates and graduates are spending more time on sending direct messages rather than viewing direct messages. The results of this research paper can be suitable for social media companies, academicians, and social reformers to utilize them in a more positive and coherent manner.